Security, International Security, Islamic Jurisprudence and the Burden of Proof (Global Journal of Human-Social Science, 2015)
Security is vital to subsistence and survival of individuals and communities. It guarantees conducive environment and affords opportunity to live and pursue a meaningful life beyond the merely animal. However, it is threatened as terrorists groups emerged in number and operate dangerously in the name of Islam. Jihad is the ethos; suicide and arms' attack are modus operandi. Innocent people and institutions are the victims. Is this truly Islamic? This is a challenge to Islamic jurisprudence and a burden to contemporary Muslim jurists. Who is (are) the architect(s) of the terrorist groups, Islam, Muslims or political super-powers? Here lies burden of proof? The present work attempts to explore these posers.
Keywords: security; jihad; maqasid al-shari’ah; terrorism; terrorists and political actors